“The Policy of Geography”: Cavour’s Considerations, European Geopolitics, and Ireland in the 1840s - Wright, Julia (Romanticism and Victorianism on the Net, 2007)
AbstractThis essay considers an 1845 English translation by “A Friend to Ireland” of a French essay on Irish politics by the Italian nationalist Count Cavour, Considerations on the Present State and Future Prospects of Ireland. Irish aspirations to national sovereignty are, in Considerations, insistently distinguished from, and represented as insignificant in relation to, a universal history in which the British Empire leads the globe towards modernity and liberalism on terms that register the ways in which universal history and geopolitics sanction opposing views of global relations and the foundations of sovereignty.